Continuing Education and Digital Skills Gap in Public Sector: Implications for National Development - Amin; Yushau Alfakoro, Abubakar S; Abiodun, Dangana Kyode (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2026)
This study surveys the role of continuing education in bridging the digital skills gap within the Nigerian public sector and its implications on national development. The study relied on the descriptive research design and exclusively on secondary data wihile adopting the Diffusion Inovation Theory as it theoretical framework. Findings from the study reveasls that the level of digital proficiency among government workers remains dismal, with significant disparities across ministries, departments, and agencies (MDAs), and between federal, state, and local levels. While basic ICT literacy, such as word processing and email, is fairly widespread, advanced competencies in areas like data analytics, cybersecurity, and e-governance are notably lacking. This deficiency undermines the effectiveness of e-government platforms and public service delivery. Although several initiatives, including NITDA’s Digital Literacy Programme and OHCSF’s e-Learning Platform, have made contributions to digital skills in public sector. However, challenges such as inadequate funding, poor infrastructure, outdated curricula, weak policy coordination, and low motivation impede progress. The study recommends targeted interventions by agencies including OHCSF, NITDA, FMCIDE, PSIN, SERVICOM, and civil service commissions to institutionalize continuing education, modernize training content, enhance awareness, increase investment in ICT, and strengthen accountability frameworks as strategic priorities for national development.